(3GdeMGSHI GdJMdjdjI (B: s (3eeWHhYI hLgI dWdHI GdSfI GdKGfjI eGSJQ LejY GdTYH (B/ s - (3HQjT, NGdOs; (3LGeYI GdLRGFQ(B3: (3cdjI GdYdhe GdEbJUGOjI, GdYdhe GdJLGQjI hYdhe GdJSjjQs ((3GdLRGFQs (3LGeYI GdLRGFQ(B3: (3cdjI GdYdhe GdEbJUGOjI, GdYdhe GdJLGQjI hYdhe GdJSjjQs, 2021)
(3eONd fXQj ddeMGSHI GdJMdjdjI , eaghe h JHhjH GdJcGdja h GdCYHGA , eMGSHI h JSjjQ GdeNRhfGJ , WQjbI GdCbSGe GdeJLGfSI , JJeI MSGH GdJcGdja, Mdhd GdCSFdI h GdJeGQjf (B.s
(3eQGLY U(B.80s
Keywords: (3GdeMGSHI GdJMdjdjIs